The ExTINGUISH Trial: A Phase-2B Randomized Placebo-Controlled Trial of Inebilizumab in Anti-NMDA Receptor Encephalitis. (5th December 2022) - Wong, Ka-Ho; Day, Gregory; Titulaer, Maarten; Torner, James; Cudkowicz, Merit; Coffey, Christopher; Lungu, Codrin; Klawiter, Eric; Singleton, J.; Mitchell, Dana; Fedler, Janel; Ecklund, Dixie; et al.
Abstract : Objective: To assess the safety and efficacy of inebilizumab in patients with anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. Background: The lack of approved therapies for NMDAR encephalitis has led to substantial variability in treatment. High-quality data is needed to guide treatment and optimize long-term outcomes in recovering patients. Inebilizumab is a humanized anti-CD19 monoclonal antibody that can be administered intravenously with good CSF penetration and high target engagement. Inebilizumab may be an efficacious treatment for NMDAR encephalitis, with the potential to achieve early robust and sustained suppression of NMDAR autoantibodies and CD19+ plasmablasts and plasma cells leading to better long-term outcomes. Design/Methods: The ExTINGUISH trial is a Phase 2B randomized double-blind placebo-controlled trial designed to evaluate the safety and efficacy of inebilizumab 300 mg for the acute treatment of moderate-to-severe NMDAR encephalitis. 120 participants will be enrolled at 20 US and two European sites (Barcelona, Spain; Rotterdam, The Netherlands). All patients will receive standard "first-line" immunotherapies prior to randomization. Cyclophosphamide IV rescue therapy will be provided after 6 weeks to patients who fail to respond to initial treatment. Motor, cognitive, and functional outcomes will be assessed over 96 weeks. Study operations will be supported via the NINDS-supported NeuroNEXT infrastructure. Results: Primary outcomes will be ascertained at 16 weeks using the change in modified Rankin scale (adjusted for rescue therapy) and accepted safety measures. Comprehensive neuropsychological tests, bedside cognitive screening tools, and quality of life/ functional indices will be measured across study participation (secondary outcomes). Clinical data will be combined with biofluid biomarkers of immune activation to inform the biologic contributors to outcomes and identify surrogate endpoints that may be used in future clinical trials (tertiary outcomes). Conclusions: ExTINGUISH Trial findings will immediately influence patient care, while informing the design and implementation of future clinical trials in autoimmune encephalitis.